Genetic and phenotypic changes related to the development of mec-independent oxacillin non-susceptibility in ST8 Staphylococcus aureus recovered after antibiotic therapy in a patient with bacteremia - (:unkn) unknown (MDPI, 2024)
The mec-independent oxacillin non-susceptible S. aureus (MIONSA) strains represent a great clinical challenge, as they are not easily detected and can lead to treatment failure. However, the responsible molecular mechanisms are still very little understood. Here, we studied four clinical ST8-MSSA-t024 isolates recovered during the course of antibiotic treatment from a patient suffering successive episodes of bacteremia. The first isolates (SAMS1, SAMS2, and SAMS3) were susceptible to cefoxitin and oxacillin. The last one (SA2) was susceptible to cefoxitin, resistant to oxacillin, lacked mec genes, and had reduced susceptibility to teicoplanin. SA2 showed higher β-lactamase activity than SAMS1. However, β-lactamase hyperproduction could not be linked to oxacillin resistance as it was not inhibited by clavulanic acid, and no genetic changes that could account for its hyperproduction were found. Importantly, we hereby report the in vivo acquisition and coexistence of different adaptive mutations in genes associated with peptidoglycan synthesis (pbp2, rodA, stp1, yjbH, and yvqF/vraT), which is possibly related with the development of oxacillin resistance and reduced susceptibility to teicoplanin in SA2. Using three-dimensional models and PBP binding assays, we demonstrated the high contribution of the SA2 PBP2 Ala450Asp mutation to the observed oxacillin resistance phenotype. Our results should be considered as a warning for physicians and microbiologists in the region, as MIONSA detection and treatment represent an important clinical challenge.
Keywords: S. aureus; MIONSA; WGS; ST8; PBP2; Staphylococcus aureus; Bacteremia